Personal Hygiene Analysis of Students and Environmental Sanitation of State Elementary School 06 Perawang Barat: Analisis Personal Hygiene Siswa dan Sanitasi Lingkungan Sekolah Dasar Negeri 06 Perawang Barat - Resky Rindra Savira; Sri Desfita; M. Kamali Zaman; Nila Puspita Sari; Zulmeliza Rasyid (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
Personal Hygiene is self hygiene to defend healthy from physically and physichologically. The impact lack of maintaining personal hygiene and sanitation school environment will cause diseases one of which is diarrhea. In Indonesia prevalence of diarrhea in 2018 with 5-14 year age group was 6,2%. In Riau Province 5-14 year age group was 5,5%. This research purpose is in generally to know student’s personal hygiene and environment sanitation of elementary school 06 Perawang Barat. This research type a qualitative research. Informan of this research consist of 6 informant they are 3 main informant, 1 key informant and 2 supporting informant. The research was done at elementary school 06 Perawang Barat from March- june 2022. The result of this research shows in this school is still found few students have long nails, however the skin and the teeth health are already good. The water condition from the quality and quantity is also already good, but in continuity have not done well. This school has already toilet never the les the cleanest is not evenly distributed. Every class has trash can and collaborate with garbage truck in waste management at elementary school 06 Perawang Barat.it is recommended to school provide education to student regarding personal hygiene, especially fingernail and hand hygiene and regarding environmental sanitation, especially latrine hygiene, and can add janitor personnel and can also make a picket schedule to turn on water so that water sustainability runs optimally.